1988
DOI: 10.1021/j100313a030
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide + carbon monoxide on rhodium(111): steady-state rates and adsorbate coverages

Abstract: Steady-state reaction rates have been measured simultaneously with XPS and UPS spectra to determine adsorbate chemical states and coverages during the NO + CO reaction and during NO decomposition on Rh( 11 1) surfaces. Steady-state NO + CO reaction rates have been determined for pressures between lo4 and 10" Torr, reactant partial pressure ratios (Pco/PNo) between 114 and 6411, and temperatures between 300 and 875 K. Near stoichiometric reactant compositions, the NO + CO reaction obeys a Langmuir-Hinshelwood m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
1

Year Published

1988
1988
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(35 citation statements)
references
References 0 publications
0
34
1
Order By: Relevance
“…Due to the scarcity and high price of Rh and Pd noble metals and increasingly stringent standard for NO emission [61][62][63], continuing improvement of noble metal catalysts for the NO-CO reaction and development of substitutes [5,61,[64][65][66].…”
Section: The No-co Reaction On Rh and Pd Catalystsmentioning
confidence: 99%
“…Due to the scarcity and high price of Rh and Pd noble metals and increasingly stringent standard for NO emission [61][62][63], continuing improvement of noble metal catalysts for the NO-CO reaction and development of substitutes [5,61,[64][65][66].…”
Section: The No-co Reaction On Rh and Pd Catalystsmentioning
confidence: 99%
“…In the reaction of NO reduction by CO in an oxygen excess condition, NO might preferentially adsorbed on the metallic Au clusters where it was dissociated to yield adsorbed N* and O* intermediates, similar to the cases of Pt and Rh as catalyst active phases [16][17][18][19]. The ability of Au to dissociate the adsorbed NO-Au, from an electronic point of view, might be resulted from the d-electrons from 5d atomic orbital in Au atoms back-donation to the 2π*antibonding orbital of adsorbed NO molecule, that activates the NO-Au complex and weakens inlet mixture, the adsorbed O* species originate from the NO dissociation or the surface lattice oxygen of TiO 2 ; however, in the case of oxygen presence in the reaction mixture, the molecular O 2 may be dissociated on the active sites to produce O* species, which may inhibit the NO dissociation, resulting in NO conversion less than 53 % at 200 ºC and 61 % at 400 ºC in the present experiment.…”
Section: Resultsmentioning
confidence: 84%
“…NO dissociation is of great importance in NO–CO reaction. Schwartz et al showed that at low temperatures (below 125–175 °C) high NO coverage inhibited NO decomposition. As the temperature increases, NO desorption becomes fast enough to further allow NO to adsorb onto a vacant rhodium site, and NO begins to dissociate.…”
Section: Surface Reaction Mechanismmentioning
confidence: 99%